Probiotic Therapy With VSL#3® in Patients With NAFLD: A Randomized Clinical Trial - Derosa, Giuseppe; Guasti, Luigina; D’Angelo, Angela; Martinotti, Chiara; Valentino, Maria Chiara; Di Matteo, Sergio; Bruno, Giacomo M.; Maresca, Andrea M.; Gaudio, Giovanni V.; Maffioli, Pamela (Frontiers in Nutrition, 2022)
Aim: to evaluate if VSL#3® [Streptococcus thermophilus BT01, Bifidobacteria (B. breve BB02, B. longum BL03, B. infantis BI04), Lactobacilli (L. acidophilus BA05, L. plantarum BP06, L. paracasei BP07, L. delbrueckii subsp. bulgaricus BD08)] therapy could improve hepatic parameters. Methods: we enrolled 60 Caucasian patients aged  18 of either sex with diagnosis of NAFLD, according to practice guidance, in a double-blind, placebo-controlled study. Patients were randomized to take placebo or VSL#3®, 2 sachets/day in the morning for 3 months. VSL#3® and placebo were self-administered. Results: we did not observe any change in BMI, circumferences, FPG, TC, LDL-C, HDL-C, and ADN with neither treatment. A statistically significant Tg decrease (p< 0.05 vs baseline, and p< 0.05 vs placebo, respectively) and Hs-CRP decrease (p< 0.05 vs baseline) was observed in the group of patients being treated with VSL#3® compared to placebo. Transaminases and -GT were significantly reduced in VSL#3® group (p<0.05 vs baseline and placebo, respectively) compared to placebo group. AST/ALT ratio and HIS were significantly lower than the VSL#3® group (p<0.05 vs baseline and placebo, respectively) compared to placebo group. All patients reported an improvement or the disappearance of hepatic steatosis. Conclusions: probiotic therapy with VSL#3® ameliorates hepatic parameters and echography grading, while also reducing Tg and the inflammatory status.